Edukasi Dan Pelatihan Pencatatan Keuangan Rumah Tangga Untuk Ibu- Ibu Kelurahan Rawa Makmur Permai - Rahman, Abdul; Putri, Annisa Rahma; Fadila, Mawar; Sakira, Hanni (Jurnal Dehasen Untuk Negeri, 2025)
The purpose of this Community Service Activity is to provide education and training to PKK Rawa Makmur Permai Village women, regarding household financial records, with the hope that household finances can be organized and good. This training is also intended to provide financial management knowledge, so that household finances are always sufficient and can have savings or investments for future needs and create prosperity for the family. The service method implemented is in the form of counseling or training on family financial management briefly and clearly, using the household financial management module. The participants in this activity were 26 participants, namely PKK women in Rawa Makmur Pernai Village. The activity is filled with the provision of material, followed by a question and answer session between the presenters and participants and exercises/practices. From the research conducted, it shows that 89% of participants are satisfied and able to understand the material, which means that the PKM activity can be declared successful.